Research on the Influence of Art Gallery Display Modes on the Meaning Generation of Artworks - Yu, Qianxun (Transactions on Social Science, Education and Humanities Research, 2026)
Art galleries are important venues for the exhibition and dissemination of artworks, and the way they are displayed directly affects people’s perception of the artworks and their understanding of their significance. Starting with the role of art gallery display methods in the formation of the meaning of artworks, this paper studies the process of generating the meaning of artworks in different types of art galleries by consulting a large amount of relevant materials and using the methods of actual visits and comparative analysis. The study suggests that display factors such as the spatial layout of the art gallery, the combination of exhibits, the signage system, the lighting design, and the visiting route all affect the expression of the meaning of the artworks. The traditional chronological arrangement, which emphasizes the development of art history, helps people understand the historical and cultural value of artworks. A thematic display can highlight the significance of a particular theme. Contextualized display is the use of a certain context to enhance the appeal of the work. At the same time, with the development of technology, the application of new technologies has also brought new opportunities for display methods, such as multimedia display, virtual reality and other technical means that make the meaning of artworks conveyed richer and more diverse. In addition, the cultural literacy, aesthetic experience and purpose of the visitors themselves will interact with the display methods, thereby influencing the meaning of the artworks. Therefore, in order to enable art galleries to better play their educational and cultural communication roles, this article puts forward the following suggestions: Fully consider the characteristics and connotations of the artworks themselves, flexibly adopt various display methods, pay attention to the needs of the audience, and establish more effective ways of communicating the meaning of the artworks.